2022
DOI: 10.1088/1361-6528/ac56b9
|View full text |Cite
|
Sign up to set email alerts
|

A high performance trench gate tunneling field effect transistor based on quasi-broken gap energy band alignment heterojunction

Abstract: In this paper, a tunneling field effect transistor based on quasi-broken gap energy band alignment (QB-TFET) is proposed and investigated by simulation method. To offering high on-state current, InGaAs/GaAsSb heterojunction with quasi-broken gap energy band alignment is applied to QB-TFET to improve the band-to-band tunneling rate. Trench gate structure and InGaAs pocket layer are applied to further increase the tunneling efficiency. To suppress the leakage current caused by the off-state tunneling path from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Figure 12c shows the characteristic curves of f T and GBW versus Vg at V d = 0.5 V. Benefiting from structural advantages, such as L-shaped channel and source, the HJTFET obtains the most outstanding frequency characteristics compared with others [21][22][23][24][25][26][27][28][29][30][31][32]. As shown in Figure 12b, the f T and GBP of the HJTFET reached the maximum values of 68.3 GHz and 7.3 GHz under the condition of V d = 0.5 V, respectively.…”
Section: Effect Of Channel Length On Device Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Figure 12c shows the characteristic curves of f T and GBW versus Vg at V d = 0.5 V. Benefiting from structural advantages, such as L-shaped channel and source, the HJTFET obtains the most outstanding frequency characteristics compared with others [21][22][23][24][25][26][27][28][29][30][31][32]. As shown in Figure 12b, the f T and GBP of the HJTFET reached the maximum values of 68.3 GHz and 7.3 GHz under the condition of V d = 0.5 V, respectively.…”
Section: Effect Of Channel Length On Device Performancementioning
confidence: 99%
“…To further improve the ON-state current, multimaterial heterojunction engineering is applied to improve the band-to-band tunneling rate [20]. Compared with conventional homojunction TFET, research shows that HJTFETs have superior performances, such as Si/SiGe heterojunction [21][22][23][24], SiGeSn/GeSn heterojunction [25], and III-V heterojunction [26][27][28][29][30][31][32]. By selecting appropriate materials to form heterojunction, on the one hand, the height and thickness of the tunneling barrier can be effectively reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its advantages of low sub-threshold swing, high on-current, and compatibility with existing CMOS technology, heterojunction TFET (HTFET) has garnered significant attention and research over the past decade [1][2][3][4] There has been experiments that showed the attractive results in HTFET, such as in Ref. [5], they reported the on-state characteristics in p type HTFET featuring a peak transconductance of 90 μS/μm at drain to source voltage of −0.3 V. On the other hand, extensive researches have also been conducted on the two phenomena based on quantum mechanical tunneling, i.e., negative differential resistance (NDR) and negative differential transconductance (NDT) [6][7][8], since the devices exhibiting NDT or NDR hold significant promise for various applications, including low-power inverter logic, memory systems, and high frequency filters [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The fabricated III-V heterostructure TFET (H-TFET) with a lateral tunneling junction has demonstrated excellent performance with sub-thermal operation, reaching down to 48 mV/decade, and a high current of 10.6 µA/µm at drain-to-source bias of 0.3 V. [4] The TCAD predicted III-V H-TFET with a trench gate and InGaAs pocket structure achieves simultaneously 921 µA/µm on-current and average subthreshold swing of 4.9 mV/dec. [5] Despite significant experimental and finite-element simulation efforts, [4][5][6][7][8][9][10][11][12] an accurate analytical model of the TFET is urgent and indispensable to provide further insight into the physics of the device and to accelerate the process of device and circuit designs. Furthermore, the potential model is the cornerstone of the capacitance and current models, [13,14] which thus needs to be modeled more accurately.…”
Section: Introductionmentioning
confidence: 99%